Endoscopic endonasal resection of a medullary cavernoma: a novel case. (2nd November 2019) - Alikhani, Puya; Sivakanthan, Sananthan; Ashour, Ramsey; Tabor, Mark; van Loveren, Harry; Agazzi, Siviero
Abstract: Brainstem cavernomas can present very challenging operative problems. Endoscopic endonasal approaches to these lesions in the mesencephalon and pons have been described. In this article the authors present the first case of a medullary cavernoma resected by an endoscopic transclival approach. A 26 year-old woman with a 1.5 cm medullary cavernoma presented with imbalance, swallowing difficulty, and right hemibody weakness. She was taken to the operating room for endoscopic endonasal transclival resection. Her pre-existing neurologic deficits worsened initially after surgery, but at three-month follow-up she had made a full neurologic recovery.